EXPERIMENTAL STUDY OF INSULATOR USING ASBESTOS COATING MATERIALS WITH DIFFERENT TEMPERATURE - Mahobia, S.K.; Kumrey, G.R. (International Journal of Engineering Technologies and Management Research, 2017)
In this paper we are study about insulator with asbestos coating material. The applied loads are as 1000 Watts, 2000Watts, 3000Watts, 4000Watts, and 5000Watts. The coated insulators are used in distribution Line, in this study we are achieving the maximum Temperature and also achieving the stable point of using insulator.